Dynamics of the Interaction Between Ceria and Platinum During Redox Processes - Luches, Paola; Gasperi, Gabriele; Sauerbrey, Marc; Valeri, Sergio; Falta, Jens; Flege, Jan Ingo (Frontiers in Chemistry, 2019)
The work is focused on understanding the dynamics of the processes which occur at the interface between ceria and platinum during redox processes, by investigating an inverse catalytic model system made of ceria epitaxial islands and ultrathin films supported on Pt(111). The evolution of the morphology, structure and electronic properties is analyzed in real-time during reduction and oxidation, using low-energy electron microscopy and spatially resolved low-energy electron diffraction. The reduction is induced using different methods, namely thermal treatments in ultra-high vacuum and in H2 as well as deposition of Ce on the oxide surface, while re-oxidation is obtained by exposure to oxygen at elevated temperature. The use of two different epitaxial systems, continuous films and nanostructures, allows determining the influence of platinum proximity on the stabilization of the specific phases observed. The factors that limit the reversibility of the observed modifications with the different oxidation treatments are also discussed. The obtained results highlight important aspects of the cerium oxide/Pt interaction that are relevant for a complete understanding of the behavior of Pt/CeO2 catalysts.